1979
DOI: 10.1063/1.438619
|View full text |Cite
|
Sign up to set email alerts
|

PES of higher temperature vapors: Lithium halide monomers and dimers

Abstract: The He (I) photoelectron spectra of ’’pure’’ monomers and dimers of the lithium halides have been obtained by using a double-oven technique to vary the dimer:monomer ratio. The lithium halide monomer spectra conform nicely to a model based on spin–orbit and ligand field interactions previously introduced. The first ionization potentials of the dimers are in each case higher than in the corresponding monomers. These conclusions are also deduced in this paper by ionic model calculations and molecular calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…1,2,12,13 The electron binding energy calibration was performed by introducing Kr gas into the experimental chamber and recording well-known 14 Kr 4p 3/2 14.00 eV and 4p 1/2 14.67 eV photoelectron lines simultaneously with alkali bromide PES. The photon energies of 90 eV, 115 eV, 119 eV, and 115 eV were used in the measurements for the LiBr, NaBr, KBr, and RbBr PES, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,12,13 The electron binding energy calibration was performed by introducing Kr gas into the experimental chamber and recording well-known 14 Kr 4p 3/2 14.00 eV and 4p 1/2 14.67 eV photoelectron lines simultaneously with alkali bromide PES. The photon energies of 90 eV, 115 eV, 119 eV, and 115 eV were used in the measurements for the LiBr, NaBr, KBr, and RbBr PES, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The outer-valence region of alkali halides has been studied extensively in past by many authors with the aid of He I excitation source and ab initio self-consisted field calculations. 1,2 Recently, Pernpointner and Knecht 3 carried out calculations of valence photoelectron spectroscopy (PES) for alkali iodides using a one-particle propagator technique in four-component framework. In their work relativistic effects were discussed in order to correctly reproduce alkali iodide spectral structure.…”
Section: Introductionmentioning
confidence: 99%
“…20, 26 The crude molecular beam ofTe is crossed by the output of a helium resonance lamp, which is guided through a Pyrex capillary tube. The output of this lamp consists predominantly of the He Ia line at 584.334 A.…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…Noble-gas calibration can be used also for angular distribution of photoelectrons [6]. Berkowitz et al reported studies of valence photoionization from alkali halide monomers and dimers [7]. They presented He I photoelectron spectra from pure LiCl monomers and dimers extracted from measured photoelectron spectra containing contributions from both species.…”
Section: Introductionmentioning
confidence: 99%